La práctica deportiva del fútbol como estrategia para la promoción de la convivencia escolar (2018)
Sport is a strategy of social intervention, and at the same time an organized activity, which tries to respond to needs of social charity and directly influence the interaction of the individuals; As pointed out, in the institutions there are different situations of violence and acts of indiscipline that make the need to educate in coexistence more relevant; This study will also be useful to determine the effectiveness of sport intervention (soccer) to improve interpersonal relationships. Therefore, the following research seeks to analyze the practice of soccer as a strategy for the promotion of school coexistence. This study is descriptive, using observation and documentary analysis to study 64 children of 5 ° A of the Bolivarian educational institution of the island of San Andrés. Based on the results, it can be concluded that sport (in this case soccer) works as a positive intermediary for the improvement of school coexistence of the children of the Bolivarian Institute